THE ORGANIZATION OF AIR TRAFFIC PLANNING - A. N. Akimov; V. V. Vorobyev; A. S. Kharlamov (Научный вестник МГТУ ГА, 2016)
The article considers the problem of civil aviation aircraft flights delays, because of the lack of efficiency of the air traffic planning. As a result, airports and airlines have financial losses. Analysis of delays at Moscow aerodromes, Tegel and Munich aerodromes are given. The principles of organization of air traffic planning system in the Russian Federation are described, as well as recommendations the use of which will improve the efficiency of the air traffic planning system in the Russian Federation.